2019
DOI: 10.1109/jphot.2019.2902726
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Full-Field Optical Sampling

Abstract: Sampling is the first step to convert analogue into digital signals and one of the basic concepts for information handling. All practical sampling systems, however, are accompanied with errors. Bandwidth-limited signals can be seen as a superposition of time-shifted sinc pulses, weighted with the sampling values. Thus, due to orthogonality, bandlimited signals can be perfectly sampled by a corresponding sinc pulse with the correct time shift. But, sinc pulses are just a mathematical construct. Sinc pulse seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…The sampled values are the integral of the sinc pulse sequence over its repetition rate, which is again Δ f s and if a coherent receiver is used, the full field can be sampled 33 . Consequently, the amplitude and phase values can be extracted by low bandwidth photodiodes and electronics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sampled values are the integral of the sinc pulse sequence over its repetition rate, which is again Δ f s and if a coherent receiver is used, the full field can be sampled 33 . Consequently, the amplitude and phase values can be extracted by low bandwidth photodiodes and electronics.…”
Section: Resultsmentioning
confidence: 99%
“…It can be shown that the presented convolution in the two cascaded modulators can be used to retrieve the phase of the sampling point by comparison with the phase of a local oscillator 33 . So if instead of a simple photodiode a coherent receiver will be used to integrate the sampling points, a full-field sampling can be accomplished.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown mathematically [1], an unlimited sinc pulse sequence is the inter-symbol interference-free superposition of equal ideal sinc pulses. Pulse sequences can be generated by filtering the frequency comb of a mode-locked laser [7], [8], by a Nyquist laser [4], by the generation of frequency combs with parametric effects [9], [10], or by one or two coupled intensity modulators that are driven with one or multiple radio frequencies [1], [13] - [23]. Especially the last method offers the possibility for integrated Nyquist pulse sources [15], [16], [19], and [20].…”
Section: Analysis Of Non-idealitiesmentioning
confidence: 99%
“…Besides communications, the temporal and spectral features of the pulse sequences like multi-wavelength operation and tunable repetition rate make them suitable to be used as a sampling source in photonic analog-to-digital (ADC) and digital-to-analog conversion (DAC) [16] - [18], [21] - [23] and as sampling pulses for the demultiplexing of Nyquist optical time-division multiplexing (OTDM) signals [24].…”
Section: Introductionmentioning
confidence: 99%